Synergies and conflicts among energy storage services - Moreira,R; Moreno,R; Strbac,G (IEEE, 2016)
Energy storage can provide services to several sectors in electricity industry, including generation, transmission and distribution and support a cost-effective transition to a low carbon electricity industry. Sharing storage plant’s energy and power capacity for multiple services portfolios leads to conflicting or synergic interactions among services. In this context, the proposed methodology determines interactions among services for distributed energy storage plants, including energy arbitrage, peak demand shaving and various balancing services, and assesses the impact that such interactions have on storage plant remunerability in a multiple service business model framework for distributed energy storage. We demonstrate that services interact differently depending on markets and system operating conditions. We also find that correlation between energy market and local system conditions is important to determine whether energy arbitrage conflicts with further services.